Biopsy-proven primary angiitis of the central nervous system mimicking leukodystrophy: A case report and review of the literature. (June 2019) - Caputi, Luigi; Erbetta, Alessandra; Marucci, Gianluca; Pareyson, Davide; Eoli, Marica; Servida, Maura; Parati, Eugenio; Salsano, Ettore
Highlights: Primary Angiitis of the Central Nervous System may mimic a leukodystrophy. Brain biopsy might be considered in case of diffuse leukoencephalopathies. It is mandatory to get a definite diagnosis when a creeping PACNS is suspected. Abstract: Primary Angiitis of the Central Nervous System (PACNS) is a rare form of idiopathic CNS vasculitis. Neuroimaging is often abnormal and characterized by multifocal brain lesions, but brain biopsy definitely confirms the diagnosis. We report the rare case of a 45-year-old female presenting with symptoms of intracranial hypertension and leukodystrophy-like neuroimaging findings. A comprehensive diagnostic work-up led to the unexpected diagnosis of a definite PACNS which was successfully treated by immunosuppressive treatment. Although rarely, PACNS can present as diffuse leukoencephalopathy on neuroimaging, and mimic even an inherited leukodystrophy. Therefore, in adults with leukodystrophy-like neuroimaging findings, careful examination of clinical and non-clinical features is mandatory to avoid missing the diagnosis of a treatable acquired disease.